Effects of Implementation of Infant‐Driven Oral Feeding Guideline on Preterm Infants' Abilities to Achieve Oral Feeding Milestones, in a Tertiary Neonatal Intensive Care Unit. (2nd March 2021) - Osman, Ahmed; Ibrahim, Mujahid; Saunders, Jean; Merheb, Roula; Moscorelli, Michele; Caretto, Vanessa; Groh‐Wargo, Sharon
Abstract : Objective: This study examines the hypothesis that infant‐driven oral feeding leads to earlier achievement of oral feeding and reduces the length of hospital stay compared with provider‐driven oral feeding in premature infants Methods: We used a retrospective chart review to compare 2 groups of premature infants born at ≤35 weeks of gestation. The control group (CG) received the Provider‐Driven Oral Feeding model and the intervention group (IG) received the Infant‐Driven Oral Feeding model. Postmenstrual age (PMA) upon achieving full oral feeding, PMA at first oral feeding, discharge weight, and length of hospital stay were compared between the groups. Results: There are 208 infants in CG and 170 infants in IG. Infants in IG were born, on average, at a lower gestational age and birth weight than infants in CG. The median PMA at full oral feeding of 35 2/7 weeks (interquartile range [IQR], 34 2/7–36 2/7) for IG is significantly lower than the median of 35 5/7 weeks (IQR, 35–36 5/7) for CG, P ‐value < 0.001. Median PMA at first oral feeding is 34 1/7 weeks for both groups. Median PMA at discharge was 36 6/7 weeks for both groups. Median discharge weights of 2509 g (IQR, 2175–2964) for IG and 2459 g (IQR, 2204–2762) for CG are not statistically different. Conclusion: Implementation of the Infant‐Driven Feeding guideline led to earlier achievement of full oral feeding by 3 days on average while maintaining the same discharge weight but did not lead to earlier hospital discharge.